The Future Initiatives of Smart communities in Baghdad as a Smart City - Alkamoosi, Noor Dheyaa; Al-Ani, Mohammed Qasim (Al-Nahrain Journal for Engineering Sciences, 2019)
Today, our cities are facing a host of challenges to accomplish the quality of life or their inhabitants. On the one hand, city planners and architects seek to preserve heritage, habits, and city peculiarities. On the other hand, it is necessary that the city is kept abreast of the rapid changes in Information and Communications Technology (ICT), Internet of Things (IoT), Artificial Intelligence (AI) and smart city concept. In Baghdad, it could be observed that there are several activities based on community initiatives, awareness campaigns, and initiatives which are self-funding from youth or funding from NGOs, and INGOs. How can we invest in such initiatives to achieve a smart city, emphasizing that the city is for the people, not a city of things? As we know that smart cities have six factors: smart (economy, governance, environment, people, mobility, and living).This paper assumes that smart communities are the seventh factor of smart cities factors which could play an essential role to apply the smartness in Baghdad. In this case, it will help to achieve making decisions and a feedback evaluation system will be subject to transparency, openness, vitality, and sustainability because it will stem from the community and ensure the sustainability in a smart city.